THE INFLUENCE OF DIGITAL PAYMENT SERVICE FEATURES ON CONSUMERS’ EASE IN TRANSACTING IN E-COMMERCE - Maulana, Fajar Bara; Nazar , Saepul; Naim; Ryando, M. Bucci; Ramdhan, Syaipul (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The development of technology at this time is so rapid, that it has given rise to many activities using technology, one of which is payment methods. Previously payment methods were made in cash, now payment methods can be made using a non-cash system. Many companies are developing non-cash payment applications which are also very popular, so the term digital payment or cashless has emerged to make transactions easier and faster. This research aims to find out the influence of digital payment service features on the convenience of consumers in making transactions in e-commerce. This type of research uses quantitative methods by collecting data using questionnaires to find respondents and testing using hypothesis testing using data analysis tools, namely IMB SPSS 26 software. This research uses a sample of 60 respondents. Sampling used purposive sampling and Roscoe’s theory technique with the characteristics of respondents being global institute students. The research results show that digital payment service features have a relationship (correlation). This can be seen in the value where the sig (2-tailed) value between the digital payment service feature (X1) and ease of transaction (Y) is 0.000 < 0.005, which means there is a significant correlation between the digital payment service feature variable and ease of transaction.